EDUCATIONAL ASPECTS OF JOSIP SLIPYI’S SPIRITUAL HERITAGE - DURDAS, Halyna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2022)
The article deals with lifeline and main areas of activity of Ukrainian Greek Catholic bishop Josip Slipyi’s – a spiritual fighter for Ukrainian sovereignty. Educational aspects of Josip Slipyi’s spiritual heritage are focused on. The influence of the family surrounding as well as social and religious personalities on the worldview formation of the future Patriarch and cultivation of Christianvirtues and love for work is explored. Period of J.Slipyi’s study is described and his formation as a theologian, scientist and educator is also explored. Bishop’s scientific and research interests are declared. Father Josip’s teaching activity has been analyzed as well as his work experience as the rector of Lviv theological seminary and later Greek Catholic Theological Academy. Josip Slipyi’s pedagogical ideas based on the principles of Christian pedagogy are pointed out. It has been clarified that main components of his educational model of study were Christian morality, spiritual values, acts of kindness and upbringing of the youth in thespirit of national idea. The main Bishop’s approaches to spiritual outlook forming of the youth are clarified. The Bishop considered artistic sphere as the main aspect of students’ spiritual development involving them in to gathering valuable history and culture monuments. Consequently, J. Slipyi longed for imparting love and respect to historical heritage among the young. He paid considerable attention to esthetical upbringing of young generation, encouraging seminarians to visit museums and libraries, choir and participating in artistic meetings. It’s been investigated that particular role for students’ preparation to social and cultural activity was played by «Reading room of theologians named after M. Shashkevych» which was renovated by father Josip while being the rector of Theological seminary. It is noticed that J. Slipyi in his educational activity taught the young not only verbally but also showed his own example. The Patriarch’sscientific heritage and pedagogical ideas during emigration period are also analyzed. It’s pointed out that the culmination of J. Slipyi’s educational activity is the foundation of Ukrainian catholic university named after Pope St. Clement. It is clarified, that personal spirituality, love for God and people, active public position of the Cardinal became the basis of moral educating of the young and his scientific achievements and pedagogical guidelines are extremely valuable in the modern conditions of education development.